Decline of cytology-based cervical cancer screening for COVID-19: a single-center Peruvian experience - Huiza Espinoza, Lilian (2022)
Introduction: Cervical cancer is the second most frequent malignant disease in the Peruvian female population, and the Papanicolaou test is its main screening tool. However, the COVID-19 pandemic can hinder cervical cancer screening, reducing its scope. Objective: To analyze the decline of Papanicolaou-based cervical cancer screening due to COVID-19 in a specialized hospital in Lima. Methods: We designed a retrospective study (from 2015 to 2020) on 355 029 Papanicolaou smears at the Hospital Nacional Madre Niño San Bartolomé. T-test and one-way ANOVA were used to define differences in the study period and Ljung-Box test with ARIMA (1,0,0) model to describe and forecast monthly expected Papanicolaou smears for 2020. Results: Throughout the six years of the study, the average Papanicolaou smears was 59 171.5 ± 8898.7 per year. However, in 2020 only 16 273 (4.58%) Papanicolaou tests were performed with a monthly mean of 1356.1 ± 684.2 (95% confidence interval 149.7 to 2861.9) (p < 0.001). The forecast showed 66 960 Papanicolaou smears for 2020 and a monthly mean of 5580 ± 129.3. Actual screenings during that year were only 16 273 Papanicolaou smears, resulting in a 76.7% reduction in cervical cancer screening during the pandemic. Conclusions: Our results suggest a dramatic decrease in cervical cancer screening based on Papanicolaou smears during 2020 in Peru due to prevention and control measures against COVID-19.